Implementasi Kebijakan Penertiban Gelandangan dan Pengemis oleh Satuan Polisi Pamong Praja Kabupaten Badung - I Nyoman Hadi Suharyana; Ni Putu Tirka Widanti; Anak Agung Gede Raka (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2022)
This study aims to analyze the implementation of the policy of managing bums and beggars By the Badung District Civil Service Police Unit based on Regional Regulation No. 7 of 2016 concerning Public Order and Community Peace. The research method used is a qualitative descriptive research method using the policy implementation model by Van Meter and Van Horn. The results showed that the implementation of the policy to control bums and beggars had not been running optimally was still experiencing obstacles. This is because the enforcement of legal sanctions has not been fulfilled, lack of human resources and facilities and infrastructure. The factors that influence the implementation have not been maximized include: resource factors, factors of the attitude of the implementers, social, economic and political environmental factors. Efforts to improve the success of implementation by adding human resources, facilities and infrastructure and improving the performance of Satpol PP with law enforcement in accordance with local regulations, causing a deterrent effect on the homeless and beggars.